A Time for Leadership - Peters, Winston (Victoria University of Wellington Law Review, 1995)
Winston Peters, the leader of the New Zealand First Party, provides his party’s ten principles by which he wishes to guide all New Zealanders in the way ahead for the Treaty negotiation process. Peters argues that it was time for all New Zealanders to rise above the Government’s failure to introduce a meaningful settlement process. First, it was important to find the proper mandate and representation of Māori. Secondly, Māori who mandate a representative must be bound by that representative’s decisions. Thirdly, the majority view of mandated Māori representation must prevail. Fourthly, there is a need for mutual decision as to the final arbiter in the absence of an amicable agreement between Māori and the Crown. Fifthly, it is important to identify the core matters in the Treaty settlement process – which are capable of settlement, and which are not? Sixthly, the matters that should be taken into consideration to arrive at a settlement process regime should be identified. Seventhly, it is important to identify the onus in the settlement process as well as where the funding for the presentation of evidence will come from. Eighthly, the regime for valuation and/or actuarial assessments on issues of cost price, value and discount must be identified. Ninthly, it must be recognised that the needs of young Māori must override those of older generations. Finally, there must be a process of education leading to a national consensus. This article also contains a question and answer session with Mr Peters.